External Sales Marketing Strategy for Bouncing Castles Company - Kútna, Dominika; Černý, Jan; Urbánek, Matyáš; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2023)
The bouncing castle industry in Central Europe is going through an unprecedented change and the demand is increasing on an annual basis. As the original reactive approach towards marketing strategy is insufficient, the thesis aims to find additional revenue streams for a local bouncing castle company based in Slovakia – Hopsaland.com with the help of emerging technologies and tools of competitive intelligence. Competitive intelligence tools provide an advanced view of the market with the attractions, reaching beyond the boundaries of the Slovak Republic. Analysis of the latest trade data provides a basis for defining emerging strategic countries for trade with the bouncing castles within the European Union and advanced competitive intelligence tools, such as web scraping, then show the uncovered opportunities on the Central European market for the company. This thesis pioneers a proactive approach towards marketing strategy in the search of revenue and finding potential customers on an example of a local company in the Slovak Republic whilst becoming agile enough to adjust to the ever-changing conditions of the entertainment market.
Vedoucí práce: Jan Černý
Závěrečná práce - Institut celoživotního vzdělávání (MBA)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet